Screening of the transcriptional regulatory regions of vascular endothelial growth factor receptor 2 (VEGFR2) in amyotrophic lateral sclerosis - Hartley Judith; Nixon Hannah; Wokke Beatrijs; Brockington Alice; Shaw Pamela J (BMC, 2007)
Abstract Background Vascular endothelial growth factor (VEGF) has neurotrophic activity which is mediated by its main agonist receptor, VEGFR2. Dysregulation of VEGF causes motor neurone degeneration in a mouse model of amyotrophic lateral sclerosis (ALS), and expression of VEGFR2 is reduced in motor neurones and spinal cord of patients with ALS. Methods We have screened the promoter region and 4 exonic regions of functional significance of the VEGFR2 gene in a UK population of patients with ALS, for mutations and polymorphisms that may affect expression or function of this VEGF receptor. Results No mutations were identified in the VEGFR2 gene. We found no association between polymorphisms in the regulatory regions of the VEGFR2 gene and ALS. Conclusion Mechanisms other than genetic variation may downregulate expression or function of the VEGFR2 receptor in patients with ALS.